Single-Cell FRET Imaging of Transferrin Receptor Trafficking Dynamics by Sfp-Catalyzed, Site-Specific Protein Labeling - Yin, Jun (2005)
SUMMARY: Fluorescence imaging of living cells depends on an efficient and specific method for labeling the target cellular protein with fluorophores. Here we show that Sfp phosphopantetheinyl transferase-catalyzed protein labeling is suitable for fluorescence imaging of membrane proteins that spend at least part of their membrane trafficking cycle at the cell surface. In this study, transferrin receptor 1 (TfR1) was fused to peptide carrier protein (PCP), and the TfR1-PCP fusion protein was specifically labeled with fluorophore Alexa 488 by Sfp. The trafficking of transferrin-TfR1-PCP complex during the process of transferrin-mediated iron uptake was imaged by fluorescence resonance energy transfer between the fluorescently labeled transferrin ligand and TfR1 receptor. We thus demonstrated that Sfp-catalyzed small molecule labeling of the PCP tag represents a practical and efficient tool for molecular imaging studies in living cells.